2022
DOI: 10.1007/s43545-021-00305-4
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in cybercrime victimization during 2010–2020: a bibliometric analysis

Abstract: Research on cybercrime victimization is relatively diversified; however, no bibliometric study has been found to introduce the panorama of this subject. The current study aims to address this research gap by performing a bibliometric analysis of 387 Social Science Citation Index articles relevant to cybercrime victimization from Web of Science database during the period of 2010–2020. The purpose of the article is to examine the research trend and distribution of publications by five main fields, including time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…PRISMA outlines essential steps for systematically reviewing scientific literature, including the selection of indexed papers from bibliographical databases while excluding nonrelevant materials (Moher et al, 2009). Ho and Luong (2022), for example, used the PRISMA guidelines in a bibliometric study to analyze the research patterns and dissemination of publications across five major fields, encompassing time, prolific authors, notable sources, active institutions, and leading countries or regions.…”
Section: Database Selection and Retrieval Of Papersmentioning
confidence: 99%
“…PRISMA outlines essential steps for systematically reviewing scientific literature, including the selection of indexed papers from bibliographical databases while excluding nonrelevant materials (Moher et al, 2009). Ho and Luong (2022), for example, used the PRISMA guidelines in a bibliometric study to analyze the research patterns and dissemination of publications across five major fields, encompassing time, prolific authors, notable sources, active institutions, and leading countries or regions.…”
Section: Database Selection and Retrieval Of Papersmentioning
confidence: 99%
“…Some of these analyses have focused on applying cyber security in specific research areas such as healthcare (Bradea et al, 2015;Jalali et al, 2019). Others focus on the bibliometric analysis of various aspects and components of cyber security such as big data, malware (Razak et al, 2016), mobile forensics (Gill et al, 2018), cybercrime victimization (Ho & Luong, 2022), cyber behavior (Serafin-Plasencia et al, 2019), cyber security, cyber parental control (Altarturi et al, 2020). Ho and Luong (2022) examined the bibliometric analysis of 387 Social Science Citation Index (SSCI) articles on cybercrime victimization on the Web of Science database during 2010-2020 (Ho & Luong, 2022).…”
Section: Figurementioning
confidence: 99%
“…Others focus on the bibliometric analysis of various aspects and components of cyber security such as big data, malware (Razak et al, 2016), mobile forensics (Gill et al, 2018), cybercrime victimization (Ho & Luong, 2022), cyber behavior (Serafin-Plasencia et al, 2019), cyber security, cyber parental control (Altarturi et al, 2020). Ho and Luong (2022) examined the bibliometric analysis of 387 Social Science Citation Index (SSCI) articles on cybercrime victimization on the Web of Science database during 2010-2020 (Ho & Luong, 2022). Their study identified research trends and distribution of publications by five main areas, including time, prolific authors, leading sources, active institutions, and leading countries/regions.…”
Section: Figurementioning
confidence: 99%
“…In 2017, the WannaCry ransomware attack affected more than 230,000 computers across 150 countries, resulting in economic losses of more than 4 billion dollars and posing a serious danger to the global education, government, finance, and healthcare sectors (Ghafur et al, 2019 ; Castillo and Falzon, 2018 ; Mohurle and Patil, 2017 ). Although there is currently no precise and universally accepted definition of cybercrime (Phillips et al, 2022 ; Holt and Bossler, 2014 ), it is generally acknowledged that the term covers both traditional crimes that are facilitated or amplified by utilising ICTs as well as new types of crimes that emerged with the advent of ICTs (Ho and Luong, 2022 ). Based on the role of technology in the commission of the crime, the most widely utilised typology divides cybercrime into cyber-dependent crime (such as hacking, distributed denial of service, and malware) and cyber-enabled crime (online fraud, digital piracy, cyberbullying) (Brenner, 2013 ; Sarre et al, 2018 ; McGuire and Dowling, 2013 ).…”
Section: Introductionmentioning
confidence: 99%